Research Progress of Gas Sensing Performance of 2D Hexagonal WO3 - Li, Yueqi; Zhou, Qin; Ding, Shoubing; Wu, Zhimin (Frontiers in Chemistry, 2021)
Metal oxide semiconductor gas sensing materials have aroused great research interest in the gas sensor field due to their outstanding physical and chemical properties, low cost and easy preparation. Among them, two-dimensional hexagonal tungsten trioxide (2D h-WO3) is especially concerned because of high sensitivity and selectivity to some gases. In this paper, the characteristics of 2D h-WO3 gas sensing materials are firstly summarized, then the effects of microstructure, oxygen vacancy and doping modification on the gas sensing performance of 2D h-WO3 are discussed in details. Finally, we propose some future research prospect of 2D h-WO3 gas sensors.